Mitosis, Focus on Calcium - Nugues, Charlotte; Helassa, Nordine; Haynes, Lee P. (Frontiers in Physiology, 2022)
The transformation of a single fertilised egg into an adult human consisting of tens of trillions of highly diverse cell types is a marvel of biology. The expansion is largely achieved by cell duplication through the process of mitosis. Mitosis is essential for normal growth, development, and tissue repair and is one of the most tightly regulated biological processes studied. This regulation is designed to ensure accurate segregation of chromosomes into each new daughter cell since errors in this process can lead to genetic imbalances, aneuploidy, that can lead to diseases including cancer. Understanding how mitosis operates and the molecular mechanisms that ensure its fidelity are therefore not only of significant intellectual value but provide unique insights into disease pathology. The purpose of this review is to revisit historical evidence that mitosis can be influenced by the ubiquitous second messenger calcium and to discuss this in the context of new findings revealing exciting new information about its role in cell division.